At the Borderline between Metal-Metal Mixed Valency and a Radical Bridge Situation: Four Charge States of a Diruthenium Complex with a Redox-Active Bis( mer-tridentate) Ligand - Mondal, Sudipta; Schwederski, Brigitte; Frey, Wolfgang; Fiedler, Jan; Záliš, Stanislav; Kaim, Wolfgang (Inorganic chemistry, 2018)
The complex ions [L Ru(μ,η :η -BL)RuL ] (1 , L = 4,4',4″-tri- tert-butyl-2,6,2',6″-terpyridine and H BL = 1,2-bis(salicyloyl)hydrazide(2-)) were isolated with PF or ClO counterions ( n = 1) and as bis(hexafluorophosphate) ( n = 2). Structural, electrochemical, and spectroscopic characterization reveals the monocation as intermediate ( K = 10 ) in the three-step reversible redox system 1 . The 1 ion has the molecule-bridged (Ru- - -Ru 4.727 Å) ruthenium centers involved in five- and six-membered chelate rings, and it exhibits long-wavelength absorptions at λ 2240, 1660, and 1530 nm (ε = 1000, 3000, and 8000 M cm , respectively), which would be compatible with a Ru Ru mixed-valent situation or with a coordinated radical ion bridge. In fact, EPR and DFT analysis of 1 reveals that the spin is equally distributed over the ligand bridge and over both metals. The oxidized paramagnetic ions 1 and 1 have been studied by H NMR and EPR and by TD-DFT supported UV-vis-NIR and MIR (mid-IR) spectroelectrochemistry. The capacity of various kinds of bis( mer-tridentate) bridging ligands (π donors or π acceptors, cyclometalated or noncyclometalated) for mediating metal-metal interactions is discussed.